Design and validation of a questionnaire to evaluate the conceptual dimension in physical education - Peña-Troncoso, S. E.; Toro Arévalo, S.; Osses Bustingorry, S.; Hernández-Mosqueira, C. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2018)
The objective of the study was to design an instrument that validly and reliably evaluated the conceptual dimension of knowledge in physical education in Chilean students in the province of Llanquihue, Los Lagos Region. The study was methodologically descriptive. A validation of content and construct was carried out; the first through an expert judgment; the second through an exploratory factor analysis with a sample of 387 students. Reliability was calculated through the internal and temporal consistency of the instrument; The first through the formula 21 of the Kuder-Richarson test; The second by applying the test-retest test through the Intraclass Correlation Coefficient (ICC), with an interval of one week. The results show adequate indexes of validity and reliability of the instrument for its use in the Chilean school population.